Metallogenic synthesis of the Syama gold district (Mali): comparative study of several gold deposits, located in the N-S trending Bagoé greenstone belt of Mali. - (:unkn) unknown (My University, 2017)
This thesis presents a comparative study of the Syama, Tabakoroni and Tellem gold deposits, located in the N-S trending Bagoé greenstone belt of Mali. Mineralization is found preferentially along the edges of millimetre- to centimetre-sized quartz, quartz-albite, quartz-ankerite, dolomite-quartz veins developed in tension gaps that formed during brittle deformation. Gold mineralization is mostly associated with pyrite in the three deposits, and also with arsenopyrite at Tabakoroni and Tellem. These sulphides are zoned with (i) an arsenic-rich core containing several albite, ankerite and rutile inclusions (less commonly, pyrrhotite) and (ii) a clear border of finely alternating As-rich and As-poor bands. Gold occurs in the form of i) invisible gold included in their crystal lattices, ii) small individual grains bound to these sulphides, frequently accompanied by sulphoantimonides, mainly tetrahedrite and chalcostibite and iii) free gold associated with quartz. The arseniferous pyrites and arsenopyrites of the Bagoé belt deposits are among the richest in invisible gold in all gold deposits in West Africa and are quite comparable to those of the Ashanti Belt in Ghana.
Keywords: African Research